Identifying the Qualities of Attention and the Attentional Style in Indoor Team Sports: A Gender Comparison - Adela Badau (Brain Sciences, 2024)
Attention is an essential psychological component in sports games, which conditions sports success. The purpose of this study was to identify the attention style (internal or external) and the weight of attention qualities depending on the practiced team sport (basketball, volleyball, or handball) and gender (female or male), in athletes aged 15–18. A total of 177 active athletes (87 female (mean age ± standard deviation: 16.07 ± 0.94 years) and 90 male (mean age ± standard deviation: 15.96 ± 0.82 years)) were involved in the study, including 62 handball players (28 female and 34 male), 58 volleyball players (30 female and 28 male) and 57 basketball players (29 female and 28 male). In the study, two questionnaires were applied: one implemented to identify the attentive style with the two dimensions internal and external (standardized), called questionnaire for the assessment of attentional style in athletes (QASA), and one designed by us, called questionnaire to identify the weights of attention qualities according to the characteristics of the practiced sport (QAQCS), aiming to identify the most relevant quality of attention, depending on the practiced sport. Cronbach’s alpha for both questionnaires was between 0.701 and 0.855. The results recorded in the present study reveal a variation in the attentional style between the groups of athletes and between genders. The results of the study highlight that in handball, girls have a predominantly external style with a total of 10.213 points; in boys’ handball, the predominant focus of attention is internal with a total score of 9.087 points. Girls’ volleyball focus of attention is predominantly external, with 8.999 points; in boys’ volleyball, the attention style is internal, registering a score of 9.713 points. In girls’ basketball, the predominant focus of attention is internal, with a total score of 8.516 points; in boys’ basketball, the external attention style is predominant, with 9.213 points. Looking at the weight of attention qualities, it was found that the most relevant for girls is concentration and mobility for handball players, stability was identified in volleyball, and distributiveness in basketball. In boys’ handball teams, mobility is the most essential, just like in basketball, and in volleyball it was found that stability has the biggest impact. ANOVA analysis highlighted statistically significant differences between groups of sports games by gender category, at both subscales of (QASA), as well as QAQCS, p < 0.05. The results of our study highlight differences between the attentional styles and their qualities in relation to the gender and the specific sport played, which determines differentiated approaches to these psychological components.
-
Keywords: attention style; external and internal dimensions of attention; gender; sport performance; qualities of attention; team sports